Modelo de roteamento de veículos aplicado ao planejamento da colheita florestal - Viana, Julyana Cristina Cândido (2017)
Harvesting is an activity of great importance in forestry enterprises, due to its high participation in the final cost of the raw material. The efficient planning of this activity is essential as it allows the optimization of operations and the reduction of costs. The objective of this work was to propose a mathematical model, based on the vehicle routing problem, to optimize the planning of the forest harvesting activity. The model aimed to reduce the total costs of the forest harvest, under inventory control constraints and average transport distance. The planning was carried out for horizon of one year, involving the harvesting of 200 stands, for the supply of two mills, one located in Telêmaco Borba and another in Ortigueira. The proposed modeling was able to determine the best cutting sequence to reduce the total costs of the forest harvest. In addition, the model proved to be effective in keeping the stock level within desirable limits and not allowing a large variation in the mean transport distance. The inclusion of the mean transport distance restriction to the model, which implied a 2,17% increase in total harvesting costs.